ANALISIS PENERAPAN PROFIL PELAJAR PANCASILA DIMENSI BERIMAN, BERTAKWA KEPADA TUHAN YANG MAHA ESA DAN BERAKHLAK MULIA DI SEKOLAH DASAR - Fanhaz Nur Tsaury; Santa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the Implementation of the Pancasila Student Profile Dimension of Faith, Devotion to God Almighty and Noble Morals in Elementary Schools in Grade IV at SD Cipambuan. This study uses a qualitative descriptive approach. The main data sources for this study are teachers, students and principals. While the secondary data sources for this study are books and articles as well as previous studies. The data collection techniques used are observation, interviews and documentation. The data analysis technique in this study is Miles and Huberman which includes data collection, data reduction, data presentation and drawing conclusions. The implementation of the dimensions of faith, devotion to God Almighty and noble character in Class IV of Cipambuan Elementary School includes the implementation of worship activities such as Duha prayer, Zuhur prayer in congregation, murojaah and the habit of reading prayers before and after studying. Furthermore, discipline by arriving at school on time, wearing clean and neat clothes, and being honest in completing school assignments. Students also shake hands with teachers when they come to school and get used to the 5S culture. Then, students care for the environment by cleaning the classroom and throwing trash in its place. Furthermore, students understand their rights and obligations both at school and participating in flag ceremonies. Cipambuan Elementary School strives to carry out activities related to the dimensions of faith, devotion to God Almighty and noble character in Class IV. However, this has not been implemented perfectly due to the lack of awareness of students who still need to be motivated.